Almost sure central limit theorems for strongly mixing and associated random variables - Khurelbaatar Gonchigdanzan (International Journal of Mathematics and Mathematical Sciences)
We prove an almost sure central limit theorem (ASCLT) for strongly mixing sequence of random variables with a slightly slow mixing rate α(n)=O((loglogn)−1−δ). We also show that ASCLT holds for an associated sequence of random variables without a stationarity assumption.